A rare case of aggressive angiomyxoma of vulva - Kurude, Vilas Namdevrao; Sinha, Surbhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Aggressive angiomyxoma is a rare, slow-growing soft tissue tumor developing from myxoid cells that usually arises in the pelvis and perineal regions of women in reproductive age, with a marked tendency to local recurrence but a low tendency to metastasize. It is often initially misdiagnosed because of its rarity. It has a marked tendency for local recurrence. Surgical resection is the treatment modality of choice for aggressive angiomyxoma. We describe a case of an aggressive angiomyxoma of vulva in a 75 year old postmenopausal woman with an asymptomatic mass on the genitalia since 3 years. Excision of the mass was done under local anaesthesia and the diagnosis was only made after histological examination. . The patient has been kept under follow-up. The etiology, presentation, diagnosis and management of this rare tumor are outlined. Angiomyxoma of vulva and vagina refers to a rare disease. Pre-operative diagnosis is difficult due to rarity and absence of diagnostic features, but it should be considered in every mass in genital, perianal and pelvic region in a woman in the reproductive age.